(De-)Criminalisation. Introduction to the Special Issue (Kriminologie - Das Online-Journal | Criminology - The Online Journal, 2025)
This special issue contains papers presented at the Criminology in North Rhine-Westphalia network’s annual conference on "(De-)Criminalisation", held in Siegen on March 21 and 22, 2024.